Assessment of estrogenic contamination and biological effects in Lake Taihu - Lu, Guanghua (Ecotoxicology (London, England), 2011)
Lake Taihu is the third largest freshwater lake in China and is contaminated with xenoestrogens associated with high population density, intensive livestock and aquatic breeding activities. A field study in Lake Taihu was conducted using the goldfish (Carassius auratus) as an indicator organism. Several biological markers were selected to assess the extent of estrogenic contamination. Changes in serum vitellogenin (VTG), and gill 7-Ethoxyresorufin-O-deethylase (EROD), glutathione-S-transferase (GST) and reduced glutathione (GSH) were measured in caged juvenile goldfish for 28 days in seven locations in northern Lake Taihu. Bioassay showed VTG increased 0.64-2.42 folds over time in goldfish collected from five stations and GSH decreased in samples from all seven stations after 7 days of exposure. EROD levels increased continually in fish collected at all the seven stations and the highest concentrations occurred at day 21. GST activity increased significantly at 7 days. The concentration of the target estrogens estrone (E(1)), 17β-estradiol (E(2)), ethinylestradiol (EE(2)), octylphenol (OP), diethylstilbestrol (DES), nonylphenol (NP) and bisphenol A (BPA) were determined in lake water at the sampling stations. Each individual estrogen concentration measured was multiplied by its relative potency to gain the estradiol equivalent (EEQ). There was an obvious correlation between the concentration of VTG and the total EEQ for all seven locations (P < 0.001). The biomarker VTG, EROD, GST and GSH assays and chemical analysis might be used to illustrate the potential risk in Lake Taihu